2018
DOI: 10.1101/391474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single-cell level and connectome-derived computational model of the Drosophila brain

Abstract: Computer simulations play an important role in testing hypotheses, integrating knowledge, and providing predictions of neural circuit functions. While considerable effort has been dedicated into simulating primate or rodent brains, the fruit fly (Drosophila melanogaster) is becoming a promising model animal in computational neuroscience for its small brain size, complex cognitive behavior, and abundancy of data available from genes to circuits.Moreover, several Drosophila connectome projects have generated a l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…First of all, it has been widely reported that inhibitory neurons increase the variability of a network [26, 27, 28, 29], and supporting evidence from connectome studies revealed that recurrent connections are abundant [30, 31]. In particular, mutual inhibition is abundant and formed locally [32, 26], possibly performing local computations [33, 22]. Secondly, evident shows that there are functional differences between feedback and mutual inhibition.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…First of all, it has been widely reported that inhibitory neurons increase the variability of a network [26, 27, 28, 29], and supporting evidence from connectome studies revealed that recurrent connections are abundant [30, 31]. In particular, mutual inhibition is abundant and formed locally [32, 26], possibly performing local computations [33, 22]. Secondly, evident shows that there are functional differences between feedback and mutual inhibition.…”
Section: Introductionmentioning
confidence: 89%
“…All simulations in this study are ran on flysim [35]. Each individual neuron was modeled as a leaky integrate- and-fire neuron: where C m is the capacitance, V the membrane potential, τ is the time constant, E L the reversal potential, and the current from the j th presynaptic neuron, and r represents the receptor.…”
Section: Methodsmentioning
confidence: 99%
“…The second stakeholder group consists of computational/theoretical neuroscientists. Several computational models have been proposed to study whole brain function [25], the early visual system [26] and visual motion detection [27,28]. Electrophysiology data has been used to identify the computation underlying photoreceptor function [29].…”
Section: Figurementioning
confidence: 99%
“…The connectomic and anatomical data currently in the FFBO platform includes all available open fly brain data from the (i) FlyCircuit [20], spanning some 20,000 neurons and 1,260,000 inferred synaptic connections [25], and (ii) the Janelia seven column Medulla EM reconstruction that includes some 500 neurons and 67,000 synapses [15,42], and (iii) the Janelia larval EM reconstruction that currently includes some 500 neurons and 138,000 synapses [43,44]. The physiological data currently in the database consists of 1.6 hours of electrophysiology recordings from photoreceptors [29,45], olfactory sensory neurons [46] and antennal lobe projection neurons [47].…”
Section: The Fruit Fly Brain Observatorymentioning
confidence: 99%
See 1 more Smart Citation